2017
DOI: 10.5114/aoms.2017.68943
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms and faster progression of cognitive impairments as predictors of risk of conversion of mild cognitive impairment to dementia

Abstract: IntroductionThe aim of this research, based on 7 years of observations, was to assess the relationship between the dynamics of changes in the realm of cognitive functions in the early stages of observations and the presence of neuropsychiatric symptoms as well as further progression of cognitive function impairments in people diagnosed with mild cognitive impairment (MCI).Material and methodsOne hundred and ninety three individuals were included in the study, all of whom referred themselves to the Mental Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
1
18
0
1
Order By: Relevance
“…This observation is in accordance with the results of previous research, carried out according to a different methodology and pertaining to earlier phases in the development of dementia, where it was shown that vascular factors increase the risk of developing dementia, but do not speed up the progression of cognitive disturbances [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…This observation is in accordance with the results of previous research, carried out according to a different methodology and pertaining to earlier phases in the development of dementia, where it was shown that vascular factors increase the risk of developing dementia, but do not speed up the progression of cognitive disturbances [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, this construct has not been empirically investigated in the context of neurocognitive research involving subjects with MCI and may account, in part, for discrepancies between various studies in rates of conversion from MCI to dementia. In addition, in most research studies focused on identification of predictors of progression from MCI to dementia (such as FDG-PET or CSF biomarkers [17] , neuropsychiatric symptoms and speed of cognitive impairment progression [18] , and white matter hyperintensities [19] ), the MCI cohorts were recruited from prevalent MCI cases. It is unclear if these predictors would have the same strength or timing if evaluated in cohorts of incident MCI.…”
Section: Discussionmentioning
confidence: 99%
“…21 One of the representative neuropsychiatric symptoms related to cognitive impairment is depression, and many cross-sectional and longitudinal studies have examined the effects of depressive symptoms on cognitive impairment. [22][23][24] Variables associated with unhealthy lifestyles, including smoking, alcohol consumption, and obesity (as measured by body mass index (BMI)), are closely associated with physical and mental disorders and, consequently, may be positively related to cognitive decline. Numerous studies have identified the relationship between alcohol consumption and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%